Interannual variations in Arctic winter temperature: the role of global scale teleconnections - Parrish, Kathryn A. (Monterey, California: Naval Postgraduate School, 2015)
To skillfully predict Arctic climate, one must fully understand the conditions influencing Arctic climate on intraseasonal, interannual, and multi-decadal time scales. This study aims to improve climate support to U.S. military operations in the Arctic by exploring the interannual variations in Arctic temperature during the winter. We have found statistically significant and dynamically plausible mechanisms for the variation in January-March (JFM) 850 hectoPascal (hPa) Arctic air temperature (T850, °C). We used JFM Arctic T850 data for 1970–2014 to analyze the associated global scale processes from 75N–90N via time series, composite, correlation, and teleconnection analyses. The patterns and teleconnections revealed in these analyses closely resembled those that have been associated with El Niño-La Niña (ENLN). Correlations between JFM Arctic T850 and ENLN, via the Multivariate El Niño-Southern Oscillation Index (MEI), were statistically significant at lead times of zero to ten months, and showed that the MEI may be a good predictor of JFM Arctic T850. These results indicate a significant potential for the improvement of long-range climate support for U.S. Navy operations in the Arctic. Approved for public release; distribution is unlimited. Lieutenant, United States Navy http://archive.org/details/interannualvaria1094545922